PENULISAN KOSAKATA BAHASA INDONESIA KE DALAM HURUF KATAKANA BAHASA JEPANG - Rahayu, Nana; Budiani, Dini; ', Septiyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study discusses the writing of Indonesian vocabulary into Japanese katakana are motivated by the many tourists who come to Indonesia, which easily can get information - Indonesian tourism information available on websites today. Website - the website is presented in Japanese, which provides a wide range of offers and explanation of the tourist attractions, cultural, and others - others regarding Indonesia. Issues addressed in this study is how the writing vocabulary Indonesian into Japanese katakana which has a [n] caudate / ng / [Î·] and which has stemmed over the sounds of the letters h / h / [Ä§] In this study, the method used is deskripftif. Data collection techniques will be studied and the data processing starting from finding and collecting websites that offer and explain the nature, culture, and the food contained in Indonesia by using a variety of languages in particular, the websites that use Japanese. Then look for the vocabulary of Indonesian origin, either using the local language and the national language of Indonesia itself by using the technique of choice directly through the discourse contained in this website that has been read and analyzed. The results of this study indicate that the use of writing vocabulary Indonesian into katakana Japanese who have a [n] caudate / ng / [Î·] and which has the sound of the letter h stemmed on / h / [Ä§] influenced by the sound of the Indonesian who later will be adjusted to the sound contained in the Japanese language itself.Keywords : vocabulary, katakana, Japanese